2016
DOI: 10.1017/s0014479716000715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Density on the Performance of Cowpea in Nigerian Savannas

Abstract: SUMMARYGrain yields of cowpea [Vigna unguiculata (L.) Walp.] in the Nigerian savannas are low even with the cultivation of improved varieties. The recommended spacing for cowpea is 75 × 20 cm with two seeds planted per stand. This corresponds to plant population of 133 333 plants ha −1 , which may not be sufficient for optimal cowpea yield. Field experiments were conducted to determine plant density effects on cowpea performance in the Northern Guinea and the Sudan savannas of Nigeria and also to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
7
18
1
3
Order By: Relevance
“…The difference in the performance of cowpea in both zones and seasons might be due to the difference in amount of rainfall received during the cropping seasons (Figure 1). The range of cowpea grain and fodder yields obtained agreed with yields of cowpea reported in earlier studies [7,21]. The effect of variety on grain yield in both zones could be partly attributed to the difference in SW and fodder yield.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The difference in the performance of cowpea in both zones and seasons might be due to the difference in amount of rainfall received during the cropping seasons (Figure 1). The range of cowpea grain and fodder yields obtained agreed with yields of cowpea reported in earlier studies [7,21]. The effect of variety on grain yield in both zones could be partly attributed to the difference in SW and fodder yield.…”
Section: Discussionsupporting
confidence: 87%
“…The Padi-Tuya variety matured later than the Apagbaala variety which gave the latter variety more growth period to accumulate enough dry matter to be partitioned into grain size, grain, and fodder yields. Kamara et al [21] also reported that differences in 100 SW of cowpea varieties contributed to the difference in grain yield among cowpea varieties. The significant effect of N fertilizer seen on grain and fodder yields and NUE in both zones could be due to the efficient use of N fertilizer for maximum economic yield.…”
Section: Discussionmentioning
confidence: 97%
“…The use of ridges spaced 75 cm apart with the recommended plant spacing of 20 cm corresponds to plant population of 133 333 plants ha −1 , which may not be sufficient for optimal cowpea yield. The low plant density resulting from wide row spacing usually leads to low yields in some grain legume crops, such as cowpea (Kamara et al, 2016). Grain yields of the widely available stress-tolerant cowpea cultivars hardly go above 1.7 t ha −1 on farmers' fields, despite the enormous gain in genetic improvement over the past three decades .…”
Section: Optimal Plant Populationmentioning
confidence: 99%
“…These varieties are usually spaced 30 cm apart to avoid overcrowding stress, while the erect types are spaced 20 cm apart to compensate for lower branching habit. To ensure that the optimum population is achieved on the widely spaced ridges, Kamara et al (2016) recommended planting two rows of cowpeas placed equidistant on the ridges. In an experiment in northern Nigeria, they planted four cowpea varieties with contrasting maturity duration in single, double and triple rows on ridges spaced 75 cm apart to achieve corresponding densities of 133 333, 266 666 and 400 000 plants ha −1 , respectively.…”
Section: Optimal Plant Populationmentioning
confidence: 99%
See 1 more Smart Citation